Fluctuation with dust of de Sitter ground state of scalar-tensor gravity - Tang, YanKe; Zhang, HongSheng; Chen, ChiYi; Li, XinZhou (Science China. Physics, mechanics & astronomy, 2014)
An exact de Sitter solution of scalar-tensor gravity is found in our recent work, in which the non-minimal coupling scalar is rolling along a non-constant potential. Based on this solution, a dust-filled FRW universe is explored in frame of scalar-tensor gravity in this article. The effective dark energy induced by the sole non-minimal scalar can be quintessence-like, phantom-like, and more significantly, can cross the phantom divide. The rich and varied properties of scalar-tensor gravity even with only one scalar is shown.